2017
DOI: 10.18632/oncotarget.20277
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of microRNA expression levels in pancreatic adenocarcinoma: a review of the literature

Abstract: BackgroundClinical and pathologic markers of prognosis and patterns of failure help guide clinicians in selecting patients for adjuvant therapy after surgical resection for pancreatic adenocarcinoma (PDAC). Recent studies have reported the prognostic utility of microRNA profiling in numerous malignancies. Here, we review and summarize the current literature regarding associations between microRNA expression and overall survival in PDAC patients.Materials and MethodsWe conducted a systematic search in the PubMe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 71 publications
0
24
1
Order By: Relevance
“…There is growing evidence that miRNA expression profiles have a potential to provide tumor-specific prognostic information. Several recent works have reported associations between microRNA expression and overall survival in PDAC patients [22,57,63,64]. In our study we observed no correlation between expression of all selected miRNAs and OS or PFS (Tables 8 and 9).…”
Section: Correlation Of Clinicopathological Features Of Tumors With Mcontrasting
confidence: 49%
“…There is growing evidence that miRNA expression profiles have a potential to provide tumor-specific prognostic information. Several recent works have reported associations between microRNA expression and overall survival in PDAC patients [22,57,63,64]. In our study we observed no correlation between expression of all selected miRNAs and OS or PFS (Tables 8 and 9).…”
Section: Correlation Of Clinicopathological Features Of Tumors With Mcontrasting
confidence: 49%
“…In PDAC, similar to other tumors, the majority of tumor-related miRNAs are tumor suppressors; for example, the miR-200 family was found to be downregulated and play important roles in EMT, cell proliferation and apoptosis [34]. Other tumor suppressors include miR-26, miR-34a, and miR-192 [35]. Oncogenic miRNAs are relatively scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has indicated that the dysregulation of miRNA was a frequent event in many cancer types, including PC . MiRNA has recently been shown to mediate resistance to anticancer agents in PC.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has indicated that the dysregulation of miRNA was a frequent event in many cancer types, including PC. [23] MiRNA has recently been shown to mediate resistance to anticancer agents in PC. For instance, miRNA-210 was down-regulated in gemcitabine-resistant PC cells, and miRNA-210 overexpression enhanced the sensitivity of PC cells to gemcitabine.…”
Section: Discussionmentioning
confidence: 99%